A Descriptive Study on Psychological and Linguistic Problems in Speaking of Speaking I Course Students of English Department FKIP Lambung Mangkurat University in Academic Year 2015/2016. - Syaiputri, Rizky Amalia (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2018)
Students may face some problems in speaking because of the nature of speaking itself which requires real-time exposure. They might become anxious on speaking and face linguistic problems since speaking is spontaneous. Thus, this research is aimed to find out EFL studentsâ speaking anxiety and linguistic problems. This research is a descriptive research design. The researchâs population was 94 English Department FKIP Lambung Mangkurat University students who take Speaking I Course in academic year 2015/2016. 50 subjects from two classes were selected as the researchâs subjects through cluster purposive sampling. The instruments used were observations and questionnaires. The research used quantitative-qualitative approach. From data analysis, it is found: (1)78% of the subjectsâ speaking anxiety level is moderate, and it shows facilitative anxiety since they are motivated to practice speaking and their participation in speaking class is fairly good, (2) the subjects also face linguistic problems, which are incorrect grammar (36.54%), lack of vocabulary (32.16%), and mispronunciation (31.40%) in speaking. Based on the research findings, it is suggested to the lecturer to create varied and fun speaking activities, and to give positive reinforcement to students. Further, lecturer needs to conduct immediate oral feedback or if possible peer oral feedback to help students recognize their linguistic problems. Students are suggested to always practice speaking English. For future researchers, it is suggested to include larger samples and use more instruments.